RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB DI SMP NEGERI 1 WOLOWARU KABUPATEN ENDE - Wilhelmus Welu; Benediktus. Y. Bhae; Kristianus Jago Tute (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
The current problem is that PPDB (New Student Admission) is still carried out conventionally, this results in data recorded in the applicant's book and processing this data takes a long time. The author uses website-based technology as a service provided by the internet to improve services to prospective students by using the PHP and MYSQL programming languages, so that prospective students can find out information about registration and registering without having to go to school but simply access the website. The author believes that prospective students simply follow the new student registration procedure using the web-based PPDB. Students can be easily selected based on their performance in exams, can improve work effectiveness, and provide information quickly and effectively, because this system does not take long to enter prospective new student data and generate reports.